Evaluation of vector systems and promoters for overexpression of the acarbose biosynthesis gene acbC in Actinoplanes sp. SE50/110 - Schaffert, Lena (Microb Cell Fact, 2019)
BACKGROUND: Actinoplanes sp. SE50/110 is a natural producer of acarbose. It has been extensively studied in the last decades, which has led to the comprehensive analysis of the whole genome, transcriptome and proteome. First genetic and microbial techniques have been successfully established allowing targeted genome editing by CRISPR/Cas9 and conjugal transfer. Still, a suitable system for the overexpression of singular genes does not exist for Actinoplanes sp. SE50/110. Here, we discuss, test and analyze different strategies by the example of the acarbose biosynthesis gene acbC. RESULTS: The integrative φC31-based vector pSET152 was chosen for the development of an expression system, as for the replicative pSG5-based vector pKC1139 unwanted vector integration by homologous recombination was observed. Since simple gene duplication by pSET152 integration under control of native promoters appeared to be insufficient for overexpression, a promoter screening experiment was carried out. We analyzed promoter strengths of five native and seven heterologous promoters using transcriptional fusion with the gusA gene and glucuronidase assays as well as reverse transcription quantitative PCR (RT-qPCR). Additionally, we mapped transcription starts and identified the promoter sequence motifs by 5′-RNAseq experiments. Promoters with medium to strong expression were included into the pSET152-system, leading to an overexpression of the acbC gene. AcbC catalyzes the first step of acarbose biosynthesis and connects primary to secondary metabolism. By overexpression, the acarbose formation was not enhanced, but slightly reduced in case of strongest overexpression. We assume either disturbance of substrate channeling or a negative feed-back inhibition by one of the intermediates, which accumulates in the acbC-overexpression mutant. According to LC–MS-analysis, we conclude, that this intermediate is valienol-7P. This points to a bottleneck in later steps of acarbose biosynthesis. CONCLUSION: Development of an overexpression system for Actinoplanes sp. SE50/110 is an important step for future metabolic engineering. This system will help altering transcript amounts of singular genes, that can be used to unclench metabolic bottlenecks and to redirect metabolic resources. Furthermore, an essential tool is provided, that can be transferred to other subspecies of Actinoplanes and industrially relevant derivatives. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12934-019-1162-5) contains supplementary material, which is available to authorized users.